Resistensi Masyarakat Terhadap Pertambangan Timah Di Laut (Studi Kasus: Desa Batu Beriga, Provinsi Kepulauan Bangka Belitung) - Putri, Aliyah; Putri Cahyani, Yolanda; Fariza Yulianti Saputri, Aulia; Karmila (BULLET : Jurnal Multidisiplin Ilmu, 2024)
This study examines the resistance of the Batu Beriga Village community to marine mining in their area. The main focus of this study is to evaluate the impact of marine mining activities and examine community responses to policies that have been implemented by the government. The results showed that the people of Batu Beriga Village refused to reject marine mining activities, because they were worried about the impact on their main livelihood as fishermen. This refusal is reflected in their request to the government to revoke the Mining Business License (IUP), as well as replace the Regional Spatial Plan (RTRW) that supports community welfare.